Newly Synthesized Lignin Microparticles as Bioinspired Oral Drug-Delivery Vehicles: Flavonoid-Carrier Potential and In Vitro Radical-Scavenging Activity - Donika Ivanova; Monika Toneva; Evgeni Simeonov; Biliana Nikolova; Severina Semkova; Georgi Antov; Zvezdelina Yaneva (MDPI AG, 2023)
The aim of the present study was to synthesize lignin microparticles, to evaluate their physicochemical, spectral, morphological and structural characteristics, to examine their encapsulation and in vitro release potential and behaviour towards the flavonoid morin in simulated physiological medium and to assess the in vitro radical-scavenging potential of the morin-loaded lignin microcarrier systems. The physicochemical, structural and morphological characteristics of alkali lignin, lignin particles (LP) and morin-encapsulated lignin microparticles (LMP) were determined based on particle size distribution, SEM, UV/Vis spectrophotometric, FTIR and potentiometric titration analyses. The encapsulation efficiency of LMP was 98.1%. The FTIR analyses proved that morin was successfully encapsulated in the LP without unexpected chemical reactions between the flavonoid and the heteropolymer. The in vitro release performance of the microcarrier system was successfully mathematically described by Korsmeyer-Peppas and the sigmoidal models outlining the general role of diffusion during the initial stages of the in vitro release process in simulated gastric fluid (SGF), and the predominant contribution of biopolymer relaxation and erosion was determined in simulated intestinal medium (SIF). The higher radical-scavenging potential of LMP, as compared to that of LP, was proven via DPPH and ABTS assays. The synthesis of lignin microcarriers not only provides a facile approach for the utilization of the heteropolymer but also determines its potential for the design of drug-delivery matrices.